The Nexus between Types of Innovation and Marketing Performance of SME in an Emerging Economy - Afriyie, Samuel; Duo, Jianguo; Appiah, Kingsley; Musah, Abdul-Aziz Ibn (International Review of Management and Marketing, 2018)
Nowadays the practice in which businesses find themselves becomes unknown, innovation types have been seen as a critical element in an organizational growth of companies. This paper intends to cross -examine the interrelation between innovation types and SME marketing performance in a growing economy of Ghana. The research used quantitative methods, in which four research hypotheses were formulated and tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). In all, 437 respondents of SME composed data through a questionnaires survey sight in the cities of Kumasi and Accra respectively in Ghana. The study outcomes identified the usefulness of a strong and meaningful impact between the types of innovation namely Product, Process, Marketing and Organization and SME marketing performance of a developing economy. The paper explores to add to the limited knowledge of SME in the perspective of innovation types literature relationship to the marketing performance in a developing economy. Studies conducted, consistently endeavor to determine the connection between the types of innovation and the firm performance and neglecting the marketing performance viewpoint. Hence, this research offers a specialized focus on the types of innovation and its relationship via SME marketing performance in a developing economy. Furtherance, executing critical issues to business managers/owners when devising approaches to organizational firm performance.